ANALYSIS OF CUSTOMER SATISFACTION AT XYZ WORKSHOP SERVICES WITH SERVQUAL ANALYSIS AND IMPORTANCE PERFORMANCE ANALYSIS - Wiyogo (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2013)
About workshop services at XYZ activity that has been given, there are still customer dissatisfaction like clean toilets, availability of benches / chairs in the waiting room, the air circulation in the waiting room. Customer complaints are an indicator of the workshop management to improve its services. Measurement of performance and expectations based on customers satisfaction was conducted using SERVQUAL to know the value gap, which is the value of the difference between what being performed to services that have been received with expectations based on customer ratings. To map the improvement priority, the method of Importance Performance Analysis is used. From IPA, P20 variable is obtained, with value X 'of 2.89 and Y' with 4.14, P25 variable with values of X 'and Y 2.86' to 4.17, P26 variables with X 'with 2.51 and Y '4.09 and P35 variable with a value of 2.69 X and Y' is a factor of 4.11. Those are the improvement priorities.